Changes in High-Density Lipoprotein Cholesterol Efflux Capacity After Bariatric Surgery Are Procedure Dependent. Issue 1 (January 2018) - Heffron, Sean P.; Lin, Bing-Xue; Parikh, Manish; Scolaro, Bianca; Adelman, Steven J.; Collins, Heidi L.; Berger, Jeffrey S.; Fisher, Edward A.
Abstract : Objective—: High-density lipoprotein cholesterol efflux capacity (CEC) is inversely associated with incident cardiovascular events, independent of high-density lipoprotein cholesterol. Obesity is often characterized by impaired high-density lipoprotein function. However, the effects of different bariatric surgical techniques on CEC have not been compared. This study sought to determine the effects of Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) on CEC. Approach and Results—: We prospectively studied severely obese, nondiabetic, premenopausal Hispanic women not using lipid medications undergoing RYGB (n=31) or SG (n=36). Subjects were examined before and at 6 and 12 months after surgery. There were no differences in baseline characteristics between surgical groups. Preoperative CEC correlated most strongly with Apo A1 (apolipoprotein A1) concentration but did not correlate with body mass index, waist:hip, high-sensitivity C-reactive protein, or measures of insulin resistance. After 6 months, SG produced superior response in high-density lipoprotein cholesterol and Apo A1 quantity, as well as global and non-ABCA1 (ATP-binding cassette transporter A1)–mediated CEC ( P =0.048, P =0.018, respectively) versus RYGB. In multivariable regression models, only procedure type was predictive of changes in CEC ( P =0.05). At 12 months after SG, CEC was equivalent to that of normal body mass index control subjects, whereas it remained impaired after RYGB. Conclusions—: SG and RYGB produce similar weight loss, but contrasting effects on CEC. These findings may be relevant in discussions about the type of procedure that is most appropriate for a particular obese patient. Further study of the mechanisms underlying these changes may lead to improved understanding of the factors governing CEC and potential therapeutic interventions to maximally reduce cardiovascular disease risk in both obese and nonobese patients. Abstract : Supplemental Digital Content is available in the text.